Study of Risk Factors for Toxoplasma gondii infection in Tripoli - Sumaya Elgodwi (AlQalam Journal of Medical and Applied Sciences, 2017)
Background and Objective: Toxoplasmosis is caused by Toxoplasma gondii is an obligate intracellular parasite which infects both humans and animals as a zoonotic pathogen wide spread in nature. This study was aimed at comparing the prevalence of toxoplasmosis in human at random population and hemodialysis patients as immunocompromised individuals, and identify risk factors that affect infection rate in different areas from Tripoli by using questionnaire. Methods: Serum samples of 2170 were collected from human population, out of it 50 serum samples from hemodialysis patients during the period from February 2016 to November 2016, were examined for the presence of antibodies of Toxoplasma gondii (Immunoglobulin G ) by immunoassay system. The seroprevalence in hemodialysis patients of Toxoplasmosis was (52%). Results: Age, study level, occupation, blood transfusion, marital status, problems during pregnancy, congenital disorder, and hemodialysis disease were statistically significantly associated with infection rates. The gender, contact with cats and dogs, source of drinking water and barbecue eating were not associated with infection. Conclussion: To conclude, with the publication of health education and disease definition will be recorded infection reduced, hemodialysis patients who are susceptible to Toxoplasma infection. Therefore, patients undergoing hemodialysis should be screened for Toxoplasma.